Hepatitis delta virus persists during liver regeneration and is amplified through cell division both in vitro and in vivo - Giersch, Katja; Urban, Stephan (Gut, 2019)
Objective Hepatitis delta virus (HDV) was shown to persist for weeks in the absence of HBV and for months after liver transplantation, demonstrating the ability of HDV to persevere in quiescent hepatocytes. The aim of the study was to evaluate the impact of cell proliferation on HDV persistence in vitro and in vivo. Design Genetically labelled human sodium taurocholate cotransporting polypeptide (hNTCP)-transduced human hepatoma(HepG2) cells were infected with HBV/HDV and passaged every 7 days for 100 days in the presence of the entry inhibitor Myrcludex-B. In vivo, cell proliferation was triggered by transplanting primary human hepatocytes (PHHs) isolated from HBV/HDV-infected humanised mice into naïve recipients. Virological parameters were measured by quantitative real time polymerase chain reaction (qRT-PCR). Hepatitis delta antigen (HDAg), hepatitis B core antigen (HBcAg) and cell proliferation were determined by immunofluorescence. Results Despite 15 in vitro cell passages and block of viral spreading by Myrcludex-B, clonal cell expansion permitted amplification of HDV infection. In vivo, expansion of PHHs isolated from HBV/HDV-infected humanised mice was confirmed 3 days, 2, 4 and 8 weeks after transplantation. While HBV markers rapidly dropped in proliferating PHHs, HDAg-positive hepatocytes were observed among dividing cells at all time points. Notably, HDAg-positive cells appeared in clusters, indicating that HDV was transmitted to daughter cells during liver regeneration even in the absence of de novo infection. Conclusion This study demonstrates that HDV persists during liver regeneration by transmitting HDV RNA to dividing cells even in the absence of HBV coinfection. The strong persistence capacities of HDV may also explain why HDV clearance is difficult to achieve in HBV/HDV chronically infected patients.
Published online first 7 December 2017
Gesehen am 02.02.2021